More or less Maddy - Genova, Lisa (New York : Scout Press, 2025)
"A breathless, riveting novel about a young woman diagnosed with bipolar disorder who rejects the stability and approval found in a traditionally "normal" life for a career in stand-up comedy. Maddy Banks is just like any other stressed-out freshman at NYU. Between schoolwork, exams, navigating life in the city, and a recent breakup, it's normal to be feeling overwhelmed. It doesn't help that she's always felt like the odd one out in her picture-perfect Connecticut family. But Maddy's latest low is devastatingly low, and she goes on an antidepressant. She begins to feel good, dazzling in fact, and she soon spirals high into a wild and terrifying mania that culminates in a diagnosis of bipolar disorder. As she struggles to find her way in this new reality, navigating the complex effects bipolar has on her identity, her relationships, and her life dreams, Maddy will have to figure out how to manage being both too much and not enough. With her signature "deep empathy and insight" (Booklist), Harvard-trained neuroscientist and New York Times bestselling author Lisa Genova has crafted another profoundly moving novel that makes complicated mental health issues accessible and human. More or Less Maddy is destined to become another classic like Still Alice"--